2023
DOI: 10.1590/0103-8478cr20210731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thawing temperature on sperm motility, structure, and metabolism of frozen bovine semen

Abstract: The heating rate used during semen thawing plays an important role in reducing structural and functional damage to spermatozoa. In this study, we evaluated the influence of thawing temperature on semen quality, reactive oxygen species (ROS) production, and mitochondrial activity of cryopreserved bovine semen. A total of 195 straws of 0.5 mL from five Holstein Friesian bulls were used (39 straws per bull). Samples underwent 8 to 22 years of storage; they were processed under a standard protocol with tris-egg yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, the thawing of semen decreases the plasma membrane integrity, causes an early acrosomal reaction, and reduces sperm quality (Zenteno et al, 2023). Higher thawing temperature than optimum increased acrosomal damage, a rise in sperm metabolic rate (Borah et al, 2015), mitochondrial activity to produce more ATP, and the consequence is higher ROS production (Khalil et al, 2018), followed by hyperactivity and induce sperm death (Zenteno et al, 2023). In this study, the temperature of 39ºC result in an improvement in sperm quality than thawing at 37ºC.…”
Section: The Thawing Temperaturesmentioning
confidence: 63%
See 1 more Smart Citation
“…However, the thawing of semen decreases the plasma membrane integrity, causes an early acrosomal reaction, and reduces sperm quality (Zenteno et al, 2023). Higher thawing temperature than optimum increased acrosomal damage, a rise in sperm metabolic rate (Borah et al, 2015), mitochondrial activity to produce more ATP, and the consequence is higher ROS production (Khalil et al, 2018), followed by hyperactivity and induce sperm death (Zenteno et al, 2023). In this study, the temperature of 39ºC result in an improvement in sperm quality than thawing at 37ºC.…”
Section: The Thawing Temperaturesmentioning
confidence: 63%
“…The thawing at 37 °C 20 s to 70 °C 12 s has not affected the midpiece and sperm head morphometry (Demirhan et al, 2020). However, the thawing of semen decreases the plasma membrane integrity, causes an early acrosomal reaction, and reduces sperm quality (Zenteno et al, 2023). Higher thawing temperature than optimum increased acrosomal damage, a rise in sperm metabolic rate (Borah et al, 2015), mitochondrial activity to produce more ATP, and the consequence is higher ROS production (Khalil et al, 2018), followed by hyperactivity and induce sperm death (Zenteno et al, 2023).…”
Section: The Thawing Temperaturesmentioning
confidence: 99%
“…According to Salih et al (2021) thawing semen at a temperature of 60 °C in 5 seconds could be an efficient strategy to maintain the quality of semen chicken that is cryopreserved. In mammal species, Zenteno et al (2023) found that the motility of bovine spermatozoa was found to be higher at a thawing temperature of 38 °C for 30 seconds compared to 36 °C for 30 seconds, while Nisa et al (2022) found the best treatment for thawing bovine sperms to be 28 °C during 45 seconds.…”
Section: Advances In Animal Andmentioning
confidence: 99%
“…The decrease can be explained by the freezing process and reduction in temperature. Membrane damage caused by extreme temperature drops occurs due to the shrinking of the fluid in the membrane (Zenteno et al 2023). Swelling and shrinking are sperm responses to osmotic changes that can cause cell death or significant loss of membrane integrity (Mughal et al 2018).…”
Section: Viability Of Simmental Cattle Frozen Semen In Variousmentioning
confidence: 99%